Geology, structure and mineralization of the Onguati area, Karibib district, central Namibia - Viljoen, Wayne (Rhodes University, Faculty of Science, Department of Geology, 2005)
The study area is situated in the Southern Central Zone of the intracontinental Pan-African Damara Orogen, approximately 20km NNE of Navachab Gold Mine in the Karibib district of Namibia. Mesothermal vein systems with Cu-FeÂ±Au mineralization are hosted by amphibolite facies calcitic and dolomitic marbles belonging to the Navachab Member of the Karibib Formation, and are best developed around the defunct Onguati Copper Mine, Brown Mountain and Western Workings areas. The Onguati study area is located in the saddle region of a moderately-to-gently inclined anticlinorium that experienced significant flattening during NNW-SSE-directed compression. The parallelogram arrangement of ENE- and NNE-trending thrusts and reverse faults that surround the Onguati study area may have developed when the direction of greatest principle subregional stress was oriented WSW-ESE. These structures define part of a Riedel shear system and later faults may have developed in the position of R and P shears respectively. Significant strain partitioning occurred between the ductile calcitic marbles which host the best developed, shear-related vein systems and the more competent dolomitic marbles. The thickness distributions of veins in the marbles of the Onguati Mine, Brown Mountain and Western Workings areas conform to a fractal or power-law distribution, The most intensely mineralized vein systems in the Onguati Mine and Western Workings calcitic marbles share similar low fractal dimensions (D-values) of 0.41 and 0.37 respectively. Veins In the calcitic and dolomitic marbles of the Brown Mountain area and in the dolomitic marbles of Western Workings have elevated D-values (>0.60) and are poorly mineralized. The low D-values Â«0.40) of the well mineralized vein systems reflect the higher degree of fracture connectivity. These vein systems were capable of efficiently draining and localizing large volumes of mineralizing fluids from crustal-scale structures. A metamorphic devolatization model is proposed where the entire Damaran metasedimentary and meta-volcanic package is seen as a large source area of very low concentrations of Cu, Au and other metals. Localization of deformation into crustal-scale faults and shear zones led to regional-scale hydrothermal fluid flow and focussing into the upstream fracture networks of the Onguati study area. Strong mineralization resulted when fluids encountered the reactive marble lithologies
Keywords: Geology -- Namibia -- Karibib; Geology, Structural -- Namibia -- Karibib; Mines and mineral resources -- Namibia -- Karibib